PENGEMBANGAN PROFESIONALITAS GURU MELALUI PENDIDIKAN PROFESI GURU (PPG) DALAM PENINGKATAN MUTU PENDIDIKAN INDONESIA. - Nika, Sakila Safa; Rahayu, Nina (Universitas Islam Negeri Sumatera Utara, 2024)
The Indonesia state continues to strive to imporove the quality of education and so far the government has taken various strategies in an effort to improve the quality of educator, both in the form of education and training programs. Teachers professional teacher are produced through academic education (S1) and teacher professional education (PPG) government teacher professional development programs are seen as an important way to improve the quality of educators, through curriculum research, infrastructure, human resources and field experience programs, to produce quality teachers wuth the competence and certification of educator. The PPG program pursued by the government will produce professional teachers who have high graduate competencies and are able to be competitive. Key words: Teacher Professionalism, Teacher Professional Education (PPG).